Tancred; Or, The New Crusade - Disraeli, Benjamin, Earl of Beaconsfield, 1804-1881 (Salt Lake City, UT : Project Gutenberg, 2006)
"Tancred; Or, The New Crusade" by Benjamin Disraeli is a novel published in 1847. Part of the Young England trilogy, it follows an idealistic young lord who abandons fashionable London society to journey to the Holy Land, seeking to understand Christianity's roots. There he encounters Eva, a Jewish financier's daughter, and becomes entangled in political intrigue involving a Lebanese emir. Through mystical visions and dangerous captivity, Tancred must confront questions about faith, civilization, and the relationship between Judaism and Christianity. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Tancred_(novel)
Release date is 2006-12-03
Produced by David Widger
Keywords: Judaism -- Relations -- Christianity -- Fiction; Christianity and other religions -- Judaism -- Fiction